The effects of specialization and sex on anterior Y-balance performance in high school athletes - Miller, M. M.; Trapp, J. L.; Pos, E. G.; Trigsted, S. M.; McGuine, T. A.; Brooks, M. A.; Bell, D. R. (Sports Health: A Multidisciplinary Approach, 2017)
Background: Sport specialization and movement asymmetry have been separately discussed as potential risk factors for lower extremity injury. Early specialization may lead to the development of movement asymmetries that can predispose an athlete to injury, but this has not been thoroughly examined. Hypothesis: Athletes rated as specialized would exhibit greater between-limb anterior reach asymmetry and decreased anterior reach distance on the Y-balance test (YBT) as compared with nonspecialized high school athletes, and these differences would not be dependent on sex. Study Design: Cross-sectional study. Level of Evidence: Level 3. Methods: Two hundred ninety-five athletes (117 male, 178 female; mean age, 15.6 ± 1.2 years) from 2 local high schools participating in basketball, soccer, volleyball, and tennis responded to a questionnaire regarding sport specialization status and performed trials of the YBT during preseason testing. Specialization was categorized according to 3 previously utilized specialization classification methods (single/multisport, 3-point scale, and 6-point scale), and interactions between specialization and sex with Y-balance performance were calculated using 2-way analyses of variance. Results: Single-sport male athletes displayed greater anterior reach asymmetry than other interaction groups. A consistent main effect was observed for sex, with men displaying greater anterior asymmetry and decreased anterior reach distance than women. However, the interaction effects of specialization and sex on anterior Y-balance performance varied based on the classification method used. Conclusion: Single-sport male athletes displayed greater anterior reach asymmetry on the YBT than multisport and female athletes. Specialization classification method is important because the 6- and 3-point scales may not accurately identify balance abnormalities. Male athletes performed worse than female athletes on both of the Y-balance tasks. Clinical Relevance: Clinicians should be aware that single-sport male athletes may display deficits in dynamic balance, potentially increasing their risk of injury.